1987
DOI: 10.1007/bf02372541
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fire on nutrients in a pine forest soil

Abstract: The effect of a hot summer fire on soil nutrient contents in the upper 2 cm of Aleppo pine forest with a dense woody understory was studied from September 1985 to May 1986.In comparison with the adjacent unburned forest, total nitrogen decreased by 25% but available forms of nitrogen were much higher. In burned and unburned soils there was a similar trend to increase and decrease in NH~--N, However, while (NO~-+ NO3 )-N decreased in the unburned soil it rose rapidly in the burned ash soil. Total phosphorus inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(85 citation statements)
references
References 17 publications
3
73
1
3
Order By: Relevance
“…Degradation of soil, which takes place after fire events, is driven by the deterioration of the soil structure [4,16,21], the loss of soil organic matter content [9,12,20,34,40] and the loss of soil mineral nutrients [10,13,14,26]. Soil microbial biomass is also affected through size reduction, impoverishment of speciographic spectra and reduction in catalytic capabilities [1,18,25].…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of soil, which takes place after fire events, is driven by the deterioration of the soil structure [4,16,21], the loss of soil organic matter content [9,12,20,34,40] and the loss of soil mineral nutrients [10,13,14,26]. Soil microbial biomass is also affected through size reduction, impoverishment of speciographic spectra and reduction in catalytic capabilities [1,18,25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several authors have also found significant reductions on microbial biomass levels after a wildfire in different ecosystems (HernĂĄndez et al, 1997;Mabuhay et al, 2006), and as suggested above, the death of microorganisms due to soil warming and the declining quality and quantity of substrate after fire may explain this decrease (Sparling et al, 1994;Vance and Nadkarni, 1990). Furthermore, most authors have reported an increase in inorganic N pools just after fire (Kutiel and Naveh, 1987;Prieto-FernĂĄndez et al, 1993) due to ash deposition and increases in soil pH and temperature that improve mineralization rates after fire (Raison, 1979). However, the decrease of mineral N levels observed in our study several years after the wildfire has also been documented in other studies throughout the world (Chorover et al, 1994;Grogan et al, 2000).…”
Section: Discussionmentioning
confidence: 87%
“…Although leguminous plants constitute a significant part of conventional cropping system, leaching and volatilization loss limit the availability of the nutrient (Oyedeji et al, 2016). Kutiel and Naveh (1987) in their study of pine forest soil reported 25% decrease in N following burning. The National Wildlife Coordinating Group (2001) also reported that volatilization loss significantly affected N, and to a lesser extent P. The slow mobility of P in soils may be responsible for its low susceptibility to loss by volatilization.…”
Section: Discussionmentioning
confidence: 99%